2019
DOI: 10.1080/09687599.2019.1580186
|View full text |Cite
|
Sign up to set email alerts
|

Constructing ‘disability’ in Myanmar: teachers, community stakeholders, and the complexity of disability models

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…For example, one of the participants mentioned teachers’ perception that students with disabilities cannot participate in STEM. Recent research showed that teachers might also consider people with disabilities as persons unable to do daily activities such as walking, revealing an understanding of disability as synonymous with physical impairment (Ware & Schuelka, 2019). Research on teacher expectations has shown that when teachers have higher expectations, they provide students with better learning opportunities (Gentrup et al., 2020; Rubie‐Davies, 2015; Timmermans et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For example, one of the participants mentioned teachers’ perception that students with disabilities cannot participate in STEM. Recent research showed that teachers might also consider people with disabilities as persons unable to do daily activities such as walking, revealing an understanding of disability as synonymous with physical impairment (Ware & Schuelka, 2019). Research on teacher expectations has shown that when teachers have higher expectations, they provide students with better learning opportunities (Gentrup et al., 2020; Rubie‐Davies, 2015; Timmermans et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…An alternative model of disability is the charity model, where persons with disability are seen as sufferers who need to be pitied and supported out of kindness, or as directed by a moral calling, such as religion (Retief & Letšosa, 2018; Ware & Schuelka, 2019). The charity model can be observed just a week after the Education Act was tabled in the Victorian parliament.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, teachers who are competent in both general and religious sciences are needed (Warsah, Aisa, & Sendi, 2020;Zubaidillah & Nuruddaroini, 2019). Teachers must have a good personality that can be a role model for students (Warsah & Uyun, 2019), and they must have a patient disposition in guiding students especially those with disabilities or those with special needs (Keane, Heinz, & Eaton, 2017;Rillotta & Alexander, 2020;Ware & Schuelka, 2019). Based on the results of a study undertaken by Sabaria (2019) regarding the strategies of Islamic education teachers in improving the psychomotor abilities of autistic students, first, the psychomotor-related competence of autistic students tends to imitate others.…”
Section: Introductionmentioning
confidence: 99%
“…In dealing with children with special needs, care givers including parents and teachers need knowledge of these children and skills in caring for and serving them (Keane et al, 2017;Rillotta & Alexander, 2020;Ware & Schuelka, 2019). Simply speaking, caregivers, parents, and teachers need to know some positive psychologybased knowledge (Warsah, 2020a) so that they can appropriately guide children with special needs.…”
Section: Introductionmentioning
confidence: 99%